2006
DOI: 10.1108/14635780610708301
|View full text |Cite
|
Sign up to set email alerts
|

Natural vacancy rates in global office markets

Abstract: PurposeThis paper seeks to contribute to knowledge of the dynamics of global office markets with an assessment of the interaction of rental growth and vacancy rates across a sample of the world's leading office markets.Design/methodology/approachEconometric methods are used to estimate the relationship between rental growth and vacancy rates (taking into account the possible simultaneity between the two variables) and these equations are then used to estimate the natural vacancy rate at an individual city leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sanderson, Farrelly, and Thoday [11] (2006) compared the natural vacancy rates of office markets in large cities worldwide and discovered that these were highest in the United States and lowest in Europe. Their analysis showed that the natural vacancy rate was low in markets where urbanization and development were actively taking place, from a spatial perspective.…”
Section: Commercial Vacancy Survival and Closurementioning
confidence: 99%
“…Sanderson, Farrelly, and Thoday [11] (2006) compared the natural vacancy rates of office markets in large cities worldwide and discovered that these were highest in the United States and lowest in Europe. Their analysis showed that the natural vacancy rate was low in markets where urbanization and development were actively taking place, from a spatial perspective.…”
Section: Commercial Vacancy Survival and Closurementioning
confidence: 99%
“…Sivitanides defines natural vacancy as the optimal inventory, taking into account the marginal costs of tenant demand and vacancy retention; that is, the vacant stock facilitates the search process for tenants and lessors [41]. Sanderson presented estimates of global and regional natural vacancy rates of 5.6% in the Asia Pacific region, 6.7% in Europe, 11.6% in North America, and 8.1% globally [42]. The office area available for conversion to residential space may be estimated by subtracting the natural vacancy from the overall office vacancy rate, as illustrated in Table 7.…”
Section: Sustainable Recovery Of Urban Spacementioning
confidence: 99%
“…Various researchers have examined vacancy; those interested in obsolescence and depreciation (Baum, 1991(Baum, , 1993Baum & McElhinney, 1997;Dunse et al, 2002;Andrew & Pitt, 2006;Crosby & Devaney 2006;Crosby et al 2011); those interested in the adaptation of vacant properties (Barlow & Gann, 1996;Beauregard, 2006;Kincaid, 2002;Heath 2001;Geraedts & van der Voordt, 2003;Agre, 2005;Langston et al, 2008;Remoy, 2010;Remoy and Wilkinson, 2012;Wilkinson and Read, 2011) those who want to map the characteristics of vacancy (Myers & Wyatt, 2004;Katyoka & Wyatt, 2008;Remoy H & Koppels, 2009); those who model the cyclical behaviour of the economy and property (Ball 2003;Barras, 2009;Wheaton 1999); and those who reflect on the medium to long-term rental adjustment process (Blank & Winnick, 1953;Wincott, 1997;Voith & Crone, 1988;Crone, 1989;Grenadier, 1995;Pissarides, 2000Pissarides, , 2005Sanderson, et al, 2006;Miceli & Sirmans, 2013). Concurrently, professional practices regularly also use relative vacancy levels (alongside absorption and take-up, rent and yield) to monitor the performance of local markets (see quarterly updates from international commercial real estate companies, CBRE, Colliers and Cushman and Wakefield, BNP Paribas, Jones Lang LaSalle).…”
Section: Theoretical Contextmentioning
confidence: 99%